Ambulatory Antibiotic Use Patterns in Bolivia: Identifying Targets for Future Antibiotic Stewardship Efforts in Latin America - Rodolfo E. Quirós; Maria E. Mesalles; Elvio D. Escobar; Juan Carlos Tapia Torrez; Sara E. Cosgrove; Valeria Fabre (Cambridge University Press, 2023)
We evaluated antibiotic use in a private health insurance network in Bolivia with two different healthcare plans. The Health Maintenance Organization plan had 29% lower antibiotic consumption and fewer broad-spectrum antibiotics prescribed than the Preferred Provider Organization. Furthermore, we identified potential targets for future antibiotic stewardship efforts.